A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae) - Maldaner, Caroline; Rafael, José Albertino (Zootaxa, 2017)
Decimiana gaucha sp. nov. is described from Rio Grande do Sul, Brazil, and illustrated. New geographical records for D. tessellata (Charpentier), D. bolivari (Chopard) and D. hebardi Lombardo retrieved from Brazilian collections and a new key to species, based on male genital characters, are presented.